Comparative Analysis of Indonesia-China High Speed Train and KTX Korea-France: A Sustainable Development for Locals or Reconfiguring Other Interests - Mulyaman, Darynaufal (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2020)
This study undermines a recent development of joint-cooperation between Indonesia and China regarding the high-speed railway and its supporting constructions. New dedicated railway, train technology, and Transit-Oriented Development (TOD) are part of the initial project, which planned concurrently along the projected area. All of these new railways and TODs are new and distant from already built residences and business centers. This study breakdown how the Indonesia-China High-Speed Train project was initiated and explaining vital factors that surround it. Reflecting on how Korea and France dealt with KTX (Korean Train Express) project, the TODs, railways, and train technology compare to the Indonesia-China High-Speed Train project, the Indonesia-China project appears not sustainable and driven by another political and economical will.